KEGIATAN LAYANAN BIMBINGAN BELAJAR BAGI SISWA KELAS VI SD NEGERI 122358 PEMATANGSIANTAR - Osco Parmonangan Sijabat; Rianita Simamora; Rektor Sianturi; Tumpal Manahara Siahaan; Rudiarman Purba (Nusantara Hasana Journal, 2023)
The tutoring service is one of the efforts to accelerate education programs in underdeveloped villages so that national education goals can be achieved. In this case a team of service lecturers and students from HKBP University Nommensen Pematangsiantar conducted tutoring services at SD Negeri 122358 Pematangsiantar specifically for class VI students. The purpose of this activity is to find out problems related to learning during the Covid-19 pandemic and their impact if the tutoring service program is implemented properly. From the results of this activity it was known that the enthusiasm of the students was very pleasant because they received tutoring services that they had never enjoyed before. This activity develops student motivation at school. The biggest hope of the students and teachers at the school is that this program can be sustainable in the future.